Pengembangan Strategi Edukasi Kontrasepsi untuk Masyarakat Nelayan - Lasarus, Marilyn; Syaekhu, Ahmad; Irma, Irma; Wibowo, Ari (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
This study aimed to develop a contraceptive education pocket book for the fishing community of Pitusingguh. The research employed a developmental approach, involving needs analysis, expert validation, and limited trials. Data were collected through in-depth interviews, focus group discussions, and questionnaires, and then analyzed using descriptive and content analysis techniques. The results showed that the developed pocket book effectively addressed the unique needs of the coastal community, with expert validation scores averaging above 4 out of 5 for accuracy, content relevance, and visual appeal. Limited trials with 15 coastal women revealed high levels of comprehension and information relevance (average scores of 4 and 4.5 out of 5, respectively). The study found that incorporating cultural sensitivity, integrating community-based health services, and implementing behavior change communication strategies were crucial in creating an acceptable and relevant educational tool. The pocket book shows potential for improving knowledge, attitudes, and practices regarding contraceptive use among the Pitusingguh fishing community, although further content adjustments are recommended to accommodate various education levels.